2017
DOI: 10.7754/clin.lab.2017.170103
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Neurodevelopmental Outcome and Serum Tau Protein Level in Neonates with Hypoxic Ischemic Encephalopathy

Abstract: Serum Tau protein level within 24 hours after birth can be used as a marker for the early diagnosis of neonatal HIE and predicting neurodevelopmental outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…In our study, neonates with moderate-severe HIE had increased serum concentrations of GFAP, NFL UCHL-1, and Tau compared to healthy controls. This study, our prior studies, and the works of others demonstrate that neonates with moderate-severe HIE undergoing hypothermia have increased concentrations of these four biomarkers compared to control subjects ( 86 , 88 , 89 ).…”
Section: Discussionsupporting
confidence: 72%
“…In our study, neonates with moderate-severe HIE had increased serum concentrations of GFAP, NFL UCHL-1, and Tau compared to healthy controls. This study, our prior studies, and the works of others demonstrate that neonates with moderate-severe HIE undergoing hypothermia have increased concentrations of these four biomarkers compared to control subjects ( 86 , 88 , 89 ).…”
Section: Discussionsupporting
confidence: 72%
“…Whether patients with more severe HI brain insults develop worsening injury with increasing tau and GFAP levels after completion of TH needs further investigation. Our results agree with other studies that have confirmed the direct association between Sarnat scores and circulating tau (19,22,23,34,44) and GFAP (21,24,34). However, our study is the first to address the potential role of TH/rewarming in the temporal trajectory of these biomarkers.…”
Section: Discussionsupporting
confidence: 92%
“…Here, we aim to study the changes attributable to TH exposure in the strength of association between traditional clinical and biochemical indicators of severity of neonatal HIE and serum biomarkers. These biomarkers included (i) BDNF and vascular endothelial growth factor (VEGF), neurotrophins essential for brain development (18,20,21); (ii) tau and GFAP, neuronal (19,22,23), and astrocytic (24) cytoskeletal markers linked to brain cell injury; and (iii) interleukin 6 (IL-6), IL-8, and IL-10, markers of inflammatory response (18,20,21); most of them studied in association to neonatal HIE previously in smaller cohorts. We hypothesized that culmination of TH changes the strength of the relationship between traditional indicators of severity of HIE and serum biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that tau protein also has predictive value after perinatal HI. Plasma and serum tau protein levels within 24 h of birth were higher in infants with severe NE than infants with moderate NE, and in cases with poor neuroimaging findings and neurodevelopmental delay [38, 39]. Interestingly, lower serum tau correlated with improved short-term behavioral scores in NE infants treated with rEpo (200 IU/kg, daily from 2 to 10 days of birth) plus therapeutic cooling, compared with infants treated with hypothermia alone [40].…”
Section: Neurobiochemical Markersmentioning
confidence: 99%
“…Further, infants with NE who do not develop CP still have lower IQ, perceptual reasoning, and verbal comprehension [2]. Therapeutic hypothermia (TH) is now routine care for infants with moderate-severe NE, to reduce death or disability [3], but needs to be started within 6 h from birth for effective neuroprotec-Increased S100B in neonatal serum <6 h of birth SS grade of NE (AUC = 0.73 for SS I/II, and 0.85 for SS II/ III), NBNA scores <35 at day 7 (r −0.585, p < 0.001) [ [38] Ancillary analysis of RCT of rEpo for neuroprotection in NE [109] 50 TH infants with SS grade II-III NE Increased tau in neonatal serum <24 h and day 5 of life Abnormal WIDEA at 1 year of age (r −0.24, p = 0.05), MRI global injury scores [39] MCP-1 Ancillary analysis of NICHD-NRN RCT of TH for NE [61] 109 infants with SS grade II-III NE Increased MCP-1 in neonatal plasma at day 7 of life Death or disability on BSID-III at 6-7 years of age (OR 3.7, 95% CI 1.42-9.61) [62] Dev Neurosci 2022; tion. This corresponds with a latent phase after reperfusion from HI that lasts ∼1-6 h, when brain metabolism transiently recovers but pathological intracellular mechanisms can be triggered, leading to mitochondrial dysfunction and delayed bulk cell death in the brain from ∼12 to 72 h [4].…”
Section: Introductionmentioning
confidence: 99%